MON-665 Hypothalamic Gliosis in Adolescents with Type 1 Diabetes and Disordered Eating Behaviors - Nip, Angel Siu Ying (J Endocr Soc, 2020)
Background: The hypothalamus and brainstem are thought to be the principal homeostatic brain areas responsible for regulating appetite and weight. Research suggests that inflammation plays a role in the onset and maintenance of eating-related maladaptive behaviors. Hypothalamic inflammation and reactive gliosis mediate disruptions in energy homeostasis, especially with obesity. Data from SEARCH in Youth for Diabetes has demonstrated high prevalence of disordered eating behaviors (DEB) including insulin omission and binge eating, in individuals with type 1 diabetes (T1D). Limited studies have used neuroimaging techniques for investigation of hypothalamic gliosis in individuals with T1D and DEB. Objectives: To determine the feasibility of assessing hypothalamic gliosis with structural MRI in adolescents with T1D with and without DEB. Research design and methods: Adolescents with T1D, aged 13-19, were invited to participate. Participants with current use of medications known to alter appetite were excluded. Participants completed the Diabetes Eating Problem Survey – Revised (DEPS-R). A score ≥ 20 was considered indicative of DEB. Height, weight and waist circumference were obtained, and BMI was calculated. HbA1C was obtained from their prior clinic visit, within 2 months of the study visit. Participants came in fasting for the MRI study visit. Basal insulin (glargine) was administered the night before, and participants on insulin infusion continued with their basal insulin infusion. Participants received rapid-acting insulin prior to the MRI study, and blood glucose was measured before and after the MRI. Mediobasal hypothalamic (MBH) gliosis was measured by T2 relaxation time. Results: Eight subjects (50% female, mean age 17.8±2.3 years) have completed the study without adverse outcomes. Mean HbA1c was 8.5% (range 7.3-10%). Five subjects screened positive for DEB. There was no significant difference in BMI between DEB and non-DEB groups. In this cohort, females had longer T2 relaxation times in left MBH than males (p=0.035). Compared to non-DEB group, participants with DEB had longer T2 relaxation time in left MBH, adjusted for sex and age (p=0.001). In this initial sample, relationships between MBH T2 relaxation times and glycemic control, BMI or waist circumference did not emerge. Conclusion: The study protocol with insulin injection and MRI to study the hypothalamic gliosis in individuals with T1D is feasible. Structural MRI indicated increased T2 relaxation times as a marker of hypothalamic gliosis in participants with DEB. Further studies with larger sample size are crucial to validate these findings and to study specific eating behaviors and their associations with MBH gliosis in individuals with T1D.